Hukum Wakaf dan Perkembangannya - Kamaruddin Kamaruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Communal ownership can be interpreted by as a gift/giving of someone to others by a person, with a target get a selfless religious service. When giving a talk on something related/relevant nothing like to exploit what is passed to people, is so that assumed by having ended contractual terms however in the growth of can comprehend by communal ownership not again simply as interpreted religious service narrow; tightly. But have been interpreted as an economic institute derestrict just religious service values, which each; every moment made ready isn’t it to whoever. Thus, he of having started to expand along with the progress of society, for example, a shop which communal ownership. So that all shall no longer be interpreted as narrow; tight something that which comprehended as does select sect.